HISTOLOGICAL EVALUATION OF REPARATIVE OSTEOGENESIS IN CRITICAL SIZE FEMORAL BONE DEFECTS IN RATS OF DIFFERENT AGES AFTER INTRODUCTION OF ALLOGRAFTS SATURATED WITH BLOOD PLASMA GROWTH FACTORS - Vorontsov, Petro; Ashukina, Nataliya; Maltseva, Valentyna; Danуshchuk, Zinaida; Nikolchenko, Olga; Samoylova, Kateryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The increase in injuries and gunshot wounds because of the war in Ukraine makes it imperative to find methods for optimizing bone regeneration and filling large-size bone defects. Aim. Study morphological features of reparative osteogenesis when critical size femoral bone defects in rats in the early reproductive and mature stages are filled with allografts saturated with blood plasma growth factors (GF). Methods. Defects (3 × 3 mm) were created in the distal femoral metaphysis of 60 white laboratory rats, 3-months-old (n = 30) and 12-months-old (n = 30). The defects were filled with bone allografts saturated with GF in the two experimental groups (AlloG+GF), and unsaturated bone allografts in the two control groups (AlloG). All groups contained 15 rats of each age. At 14, 28 and 90 days after the surgery, 5 rats from each group were sacrificed, and histological analyses were performed. Results. In the AlloG groups, excessive formation of connective tissue was observed 14 and 28 days after the surgery, most evident in the 3-monthold rats. In the AlloG+GF groups, bone formation was delayed at 14 days independent of age, while at 28 and 90 days, the area of bone trabeculae did not differ from the values in the AlloG groups. Throughout the experiment, decreases in allograft area (almost all of it was replaced by bone after 90 days) and connective tissue (completely absent in 3-month-old rats after 90 days) were observed in both AlloG+GF groups. The area of bone trabeculae increased in the period from 14 to 28 days. Conclusion. Saturating allografts with blood plasma growth factors facilitates an increase in the rate at which allografts are replaced by bone tissue, independent of the recipient’s age. However, excessive formation of connective tissues in the defect 14 and 28 days after the surgery, especially in 3-month-old rats, may negatively affect the mechanical properties of the bone, which should be considered in clinical practice.